Studi Literatur : Optimasi Perencanaan Produksi dengan Metode Goal Programming - Atika Rahmah; Siti Salamah Br Ginting; Avita Salsabila; Fanny Selfinta Perangin-angin; Mustika Nurbayeni; Nurul Fatma Dewi Mardianto; Wulan Dari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Production planning is one of the most important factors in improving business continuity. The preparation of production planning is related to the optimization of production for a particular business so that the business can operate efficiently and production activities achieve competitive prices. The preparation of production planning must consider several factors because every business has different goals that it wants to achieve. The Goal Programming method aims to minimize deviations from the targets set by the business, so that business goals can be achieved optimally. This research aims to optimize production in a company that can accomplish more than one goal. The method used in this study is Systematic Literature Review (SLR), and this study identifies 5 previous journals. The source of information used in this study is articles from national journals published between 2018-2024. The results of this study show that Goal Programming is a very effective tool in production and distribution planning in various industrial sectors.